The Structure and Operation of the World Gold Market - O'Callaghan, M. (IMF Working Papers; Working Paper, 1991)
This paper describes the structure of the world gold market, its sources of supply and demand, and how it functions. The market has three principal functions in three major locations: the New York futures market speculates on spot prices, which are largely determined in London, whereas physical gold is in large part shipped through Zurich. The market is dominated by large suppliers and gold holders, including monetary authorities. Some unique characteristics of the gold market ensure confidentiality, and as a result, there are gaps in existing knowledge and data. The paper identifies and attempts to fill these gaps.